Polymer electrolyte and preparation method thereof

By using a specific design of polymaleimide polymer electrolyte, the problem of instability and polarization risks of polymer electrolytes in the prior art is solved, and high ionic conductivity and stable battery cell performance are achieved.

CN120199884APending Publication Date: 2025-06-24BELENOS CLEAN POWER HLDG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411837463.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-22
Filing Date
2024-12-13
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

Existing polymer electrolytes are unstable at high voltages and have a risk of polarization, resulting in a decrease in the energy density and current value of the battery cell.

Method used

Using a polymer electrolyte composed of the first and second polymaleimide polymers, an electrolyte with high ionic conductivity, thermal stability and mechanical stability is prepared by designing specific polymer repeating units and molar ratios, combining thiol-ene reactant and free radical initiator.

Benefits of technology

The stability of polymer electrolyte at high voltage is achieved, the risk of polarization is reduced, the energy density and current value of the battery cell are increased, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120199884A_ABST
    Figure CN120199884A_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer electrolyte for a battery cell comprising: i) a first polymaleimide polymer comprising a first polymaleimide repeat unit of formula R3 (Q) [mu] wherein R3 is a polyether or C (H) h (CxH2x + 1) i ((CH2) [psi]) j (CH2OC (O) (CH2) [sigma]) k, i being 0 to 2; j and k are each 0 to 4; h is 4-i-j-k; the sum of h and i is 0 to 2; x is 1 to 6; psi is 1 to 10; sigma is 1 to 20; mu is at least 2; q is as shown in formula (I), wherein R2 is alkyl with 1 to 16 carbon atoms, alkenyl with 2 to 16 carbon atoms, alkynyl with 2 to 16 carbon atoms or aryl; r < 4 > is H, an alkyl group having 1 to 16 carbon atoms, an alkenyl group having 2 to 16 carbon atoms, or an alkynyl group having 2 to 16 carbon atoms; q is covalently bonded to R3 via a sulfur atom of Q; ii) a second polymaleimide polymer comprising a second polymaleimide repeating unit of formula (II) wherein R1 is H, a C1-C16 alkyl group, a C2-C16 alkenyl group, a C2-C16 alkynyl group; m is 1 to 5; m + is an alkali metal ion; and X is H, F, alkyl with 1 to 16 carbon atoms or fluoroalkyl with 1 to 16 carbon atoms. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polymer electrolytes, in particular solid electrolytes. The present invention also relates to battery cells comprising such polymer electrolytes and methods for preparing such polymer electrolytes. Background Art

[0002] The importance of batteries and other energy storage devices is growing rapidly. The rise of electric technologies, especially electric vehicles and e-scooters, requires batteries with high capacity and reasonable weight.

[0003] Regarding battery technology, current research is dedicated to new materials to improve battery safety, as well as to increase and optimize volumetric and gravimetric energy densities.

[0004] Conventional liquid electrolytes, such as those used in lithium batteries, are based on mixtures of organic solvents and lithium salts. These electrolytes have high ionic conductivity and are electrochemically stable within the voltage window of the battery. However, such liquid electrolytes are highly flammable, volatile and may leak outside the battery casing. These drawbacks can lead to critical failure, combustion and explosion of the battery.

[0005] Recently, to improve the safety of alkali metal and alkaline earth metal batteries, solid electrolytes, polymer electrolytes (e.g., gel (polymer) electrolytes) and ionic liquid electrolytes have been developed.

[0006] Gel polymer electrolytes are systems in which a liquid electrolyte is encapsulated and impregnated within a generally chemically crosslinked polymer structure. This type of electrolyte can provide relatively high ionic conductivity at a reasonable price and has high structural, thermal and mechanical stability over time. However, its ionic conductivity is still lower than that of liquid electrolytes because the structure of the crosslinked polymer tends to impede the movement of metal ions, such as lithium ions for lithium-ion batteries.

[0007] WO2022 / 055307 discloses a gel polymer electrolyte for a lithium secondary battery, which is obtained from a precursor composition comprising two crosslinking agents, a lithium salt and a small amount of an organic solvent, wherein one of the crosslinking agents comprises at least two thiol functional groups.

[0008] US2023096123 discloses a solid polymer electrolyte comprising a crosslinked polymer network. The crosslinked polymer network comprises crosslinked groups such as difunctional polyether groups and / or difunctional ionic groups, and crosslinked polyfunctional crosslinker groups, and at least one crosslinked group comprises a thioether group. Regarding the solid polymer electrolyte for conductivity, it must also comprise a dual-ion conductive salt (such as a metal salt), linked ionic groups, and / or a liquid electrolyte.

[0009] One drawback of the above electrolytes is that the polyether groups are unstable at high voltages (such as 4V and higher). Another drawback is the risk of polarization in battery cells comprising these electrolytes, which is due to the use of dual-ion conductive salts and the low lithium transference number of such electrolytes. As is known, polarization reduces the energy density of the battery cell, thereby limiting the current values available for charging and discharging the battery cell. In other words, polarization in the battery cell causes the performance of the battery cell to rapidly degrade with each charge and discharge cycle. SUMMARY OF THE INVENTION

[0010] The object of the present invention is to overcome one or more of the above drawbacks. One object of the present invention is to provide a polymer electrolyte having high ionic conductivity, especially for lithium ions. Another object is to provide a polymer electrolyte having high structural stability, electrochemical stability, thermal stability, and mechanical stability over time. Another object is to provide a polymer electrolyte substantially free of any processing solvents. Another object is to provide a polymer electrolyte for a battery cell that can reduce the risk of polarization in the battery cell, thereby improving the current values available for the battery cell, and providing a battery cell having both high performance and a long lifespan (i.e., significantly reducing or even avoiding performance degradation), especially in the case of repeated charge / discharge cycles.

[0011] Another object is to provide a method for preparing such a polymer electrolyte that has high ionic conductivity, high voltage stability up to at least 4V, and thermal and mechanical stability.

[0012] According to a first aspect of the present invention, there is provided a polymer electrolyte for a battery cell as claimed in the appended claims. The polymer electrolyte comprises a first polyimide polymer and a second polyimide polymer, or consists essentially of a first polyimide polymer and a second polyimide polymer. The first polyimide polymer contains first polyimide repeating units, or consists essentially of first polyimide repeating units. The second polyimide polymer contains second polyimide repeating units, or consists essentially of second polyimide repeating units.

[0013] The first polyimide repeating unit is as R 3 (Q) μ as shown. μ is independently at least 2, preferably in the range of 2 to 4. Q is independently as shown in formula (I):

[0014]

[0015] where

[0016] Q is covalently bonded to R via the sulfur atom of Q 3 ,

[0017] R 2 is independently C1-C 16 alkyl, C2-C 16 alkenyl, C2-C 16 alkynyl or aryl, and R 4 is independently H, C1-C 16 alkyl, C2-C 16 alkenyl, C2-C 16 alkynyl.

[0018] Advantageously, R 2 is methyl, ethyl, propyl, n-butyl, isobutyl, benzyl or styryl.

[0019] Advantageously, R 4 is H, methyl, ethyl or propyl.

[0020] R 3 is independently C(H) h (C x H 2x+1 ) i ((CH2) ψ ) j (CH2OC(O)(CH2) σ ) k or a polyether, where i is in the range of 0 to 2; j and k are independently in the range of 0 to 4; h is 4 - i - j - k; the sum of h and i is in the range of 0 to 2; x is in the range of 1 to 6; ψ is in the range of 1 to 10; and σ is in the range of 1 to 20.

[0021] Advantageously, when R 3 is a polyether, the polyether is as shown, where ω is in the range of 0 to 4, is in the range of 1 to 4, and α is in the range of 1 to 10, preferably in the range of 1 to 5.

[0022] Optionally and additionally advantageously, R 3 is -(CH2) β- wherein β is in the range of 1 to 20 (i.e., h is 2, i is 0, j is 2, k is 0). Optionally and advantageously, R 3 is C(CH2CH3)(CH2OC(O)(CH2) σ )3- (i.e., h is 0, i is 1, j is 0, and k is 3). Optionally and advantageously, R 3 is C(CH2OC(O)(CH2) σ )4- (i.e., h is 0, i is 0, j is 0, and k is 4).

[0023] The second polyimide repeating unit is shown in formula (II):

[0024]

[0025] wherein

[0026] R 1 is independently H, C1-C 16 alkyl, C2-C 16 alkenyl, C2-C 16 alkynyl;

[0027] m is independently 1 to 5;

[0028] M + is independently an alkali metal ion; and

[0029] X is independently H, F, C1-C 16 alkyl, C1-C 16 fluoroalkyl.

[0030] Advantageously, R 1 is H, methyl, ethyl or propyl.

[0031] Advantageously, X is CF3, CH3 or F.

[0032] Advantageously, the alkali metal is lithium, sodium or potassium, preferably lithium. In other words, the alkali metal ion is advantageously a lithium ion (Li + ), a sodium ion (Na + ), or a potassium ion (K + ), preferably a lithium ion.

[0033] Advantageously, the molar ratio between the first polyimide polymer and the second polyimide polymer is in the range of 5 to 95, preferably in the range of 10 to 75, more preferably in the range of 20 to 50, based on the total molar amount of each polymer in the polymer electrolyte. The inventors have found that when the molar ratio between the first polyimide polymer and the second polyimide polymer is in the range of 5 to 95, the polymer electrolyte simultaneously has excellent ionic conductivity and optimal mechanical properties.

[0034] The polymer electrolyte may further comprise a plasticizer. Advantageously, the polymer electrolyte comprises 0 - 90 wt% of a plasticizer, preferably 0 - 80 wt%, based on the total weight of the polymer electrolyte. Advantageously, when the polymer electrolyte comprises a plasticizer, it comprises 0.5 - 90 wt% of a plasticizer, such as 5 - 85 wt%, preferably 10 - 85 wt%, such as 20 - 80 wt%, more preferably 45 - 60 wt%, based on the total weight of the polymer electrolyte.

[0035] Advantageously, the plasticizer is selected from linear carbonates, cyclic carbonates, ethers and nitriles. The plasticizer is preferably a linear carbonate or a cyclic carbonate. Examples of particularly preferred plasticizers are propylene carbonate and ethylene carbonate. The polymer electrolyte may comprise two or more plasticizers, which are independently selected from linear carbonates, cyclic carbonates, ethers and nitriles.

[0036] According to a second aspect of the present invention, there is provided a battery cell as claimed in the appended claims.

[0037] The battery cell comprises a polymer electrolyte according to the first aspect of the present invention. Advantageously, the battery cell is a secondary battery cell. Advantageously, the battery cell is a lithium metal battery cell.

[0038] According to a third aspect of the present invention, there is provided a method for preparing a polymer electrolyte for a battery cell as claimed in the appended claims. The polymer electrolyte comprises a first polyimide polymer and a second polyimide polymer, or consists essentially of a first polyimide polymer and a second polyimide polymer. Advantageously, the polymer electrolyte prepared by the method according to the third aspect of the present invention is the polymer electrolyte according to the first aspect of the present invention.

[0039] The method includes the step of preparing a blend that contains a third polyimide polymer, a second polyimide polymer, a free radical initiator, and a thiol-ene reagent, where the third polyimide polymer contains a third polyimide repeating unit or consists essentially of a third polyimide repeating unit, and the second polyimide polymer contains a second polyimide repeating unit or consists essentially of a second polyimide repeating unit.

[0040] The third polyimide repeating unit is represented by formula (III):

[0041]

[0042] where R 2 and R 4 are as defined above.

[0043] The second polyimide repeating unit is represented by formula (II).

[0044] The thiol-ene reagent contains thiol groups. The number q of thiol groups is at least 2, such as 2, 3, 4, or greater.

[0045] The term "thiol group" herein refers to the functional group -SH, i.e., a sulfur atom covalently bonded to a hydrogen atom.

[0046] The number n of the third polyimide repeating units, the number q of thiol groups, and the number a of thiol-ene reagent molecules are selected such that Preferably More preferably For example, it is about 1.

[0047] Optionally, the blend further contains a processing solvent. The term "processing solvent" herein refers to a solvent used during the preparation of the polymer electrolyte, but this solvent is not present in the resulting polymer electrolyte. Advantageously, the optional processing solvent contains acetone, dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, or a combination of two or more thereof, or consists essentially of them.

[0048] The inventors unexpectedly found that the blend allows for processing without the need for a processing solvent, such as application to a substrate, thereby obtaining favorable viscosity and processing characteristics. So unexpectedly, the presence of the processing solvent in the blend is optional.

[0049] Optionally, the blend further comprises a plasticizer. The optional plasticizer is as defined above. Advantageously, the blend comprises 0.5 - 90% by weight of the plasticizer, such as 5 - 85% by weight, 10 - 85% by weight, preferably 20 - 80% by weight, such as 45 - 60% by weight, based on the total weight of the blend minus the weight of any optional processing solvent.

[0050] The term "total weight of the blend minus the weight of any optional processing solvent" as used herein, when the blend does not contain a processing solvent, refers to the as - received weight of the blend; and when the blend contains a processing solvent, refers to the weight of the blend without considering the weight of the processing solvent.

[0051] Advantageously, the free - radical initiator can initiate a thiol - ene reaction between the third polyimide repeat unit and the thiol - ene reagent. Advantageously, upon initiation, a sulfur - carbon covalent bond is formed between the third polyimide repeat unit and the thiol - ene reagent, thereby obtaining a sulfur - ether bond.

[0052] Advantageously, the blend comprises 0.05 - 1.5% by weight of the free - radical initiator, preferably 0.075 - 1.4% by weight, more preferably 0.1 - 1.25% by weight, based on the total weight of the blend minus the weight of any optional processing solvent.

[0053] Advantageously, the blend comprises 0 - 95% by weight of the processing solvent, such as 1 - 95% by weight, 5 - 92.5% by weight, preferably 10 - 90% by weight, more preferably 20 - 90% by weight, such as 50 - 90% by weight, based on the total weight of the blend including the weight of the processing solvent.

[0054] The term "total weight of the blend including the weight of the processing solvent" as used herein, when the blend does not contain a processing solvent (0% by weight of the processing solvent in the blend), refers to the as - received weight of the blend; and when the blend contains a processing solvent, refers to the weight of all components of the blend, including the processing solvent.

[0055] Advantageously, the blend comprises a total of 3 - 45% by weight of the third polyimide polymer and the thiol - ene reagent, preferably 10 - 40% by weight, based on the total weight of the blend minus the weight of any optional processing solvent.

[0056] Advantageously, the blend comprises 5 - 95% by weight of the second polyimide polymer, preferably 40 - 90% by weight, based on the total weight of the blend minus the weight of any optional processing solvent.

[0057] Advantageously, when the blend contains a plasticizer, it contains 30 - 80 wt% plasticizer, a total of 3 - 45 wt% of a third polyimide polymer and a thiol-ene reagent, 1 - 45 wt% of a second polyimide polymer, and 0.05 - 1.5 wt% of a free radical initiator, based on the total weight of the blend minus the weight of any optional processing solvent.

[0058] More preferably, when the blend contains a plasticizer, it contains 45 - 75 wt% plasticizer, a total of 5 - 40 wt% of a third polyimide polymer and a thiol-ene reagent, 2 - 40 wt% of a second polyimide polymer, and 0.1 - 1.25 wt% of a free radical initiator, based on the total weight of the blend minus the weight of any optional processing solvent.

[0059] The method further includes applying the blend to a substrate. The substrate can be any substrate, such as a Teflon sheet or glass, or can be the anode or cathode of a battery cell. The blend can be applied to the substrate by means known in the art, such as, but not limited to: casting, pressing, which can be hot pressing or cold pressing, and applying without any pressure, such as using a spatula. Advantageously, when the blend is applied to the substrate, a film of the blend is obtained.

[0060] When the blend contains a processing solvent, the method further includes removing the processing solvent, thereby obtaining a blend that is substantially free of the processing solvent.

[0061] The method further includes exposing the (substantially processing solvent-free) blend to one or more of UV irradiation, IR irradiation, or a temperature of up to 100 °C. When exposed to one or more of UV irradiation, IR irradiation, or a temperature of up to 100 °C, the thiol-ene reaction of the (substantially processing solvent-free) blend is initiated, particularly the reaction of the thiol-ene reagent with the third polyimide repeat unit, thereby obtaining a polymer electrolyte having sulfur-ether bonds, i.e., sulfur-carbon covalent bonds.

[0062] Advantageously, the thiol-ene reaction allows the blend to crosslink, particularly the third polyimide repeat unit to crosslink, thereby obtaining a polymer electrolyte having sulfur-ether bonds. In particular, a film or sheet of the polymer electrolyte is obtained on the substrate.

[0063] Advantages of the method of the present invention include that the use of processing solvents can be reduced or eliminated, which makes the method more environmentally friendly.

[0064] In the polymer electrolyte of the present invention, there is a second polyimide repeat unit and an optional plasticizer, and the advantages brought thereby include high ionic conductivity and high stability over time. In the polymer electrolyte of the present invention, there is a first polyimide repeat unit, and the advantages brought thereby include high thermal stability, structural stability, and mechanical stability over time. The overall advantage of the polymer electrolyte of the present invention is the ability to withstand high voltages, thereby allowing it to be used together with active materials that operate at high voltages.

[0065] The advantages of the battery cell of the present invention, i.e., the battery cell containing the polymer electrolyte of the present invention, include high ionic conductivity and excellent ability to withstand repeated charge / discharge, and thus have excellent lifespan. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Aspects of the present invention are described in more detail below with reference to the accompanying drawings, in which like reference numerals represent like features, and in which:

[0067] - Figure 1 showing the polymer electrolyte of the present invention;

[0068] - Figure 2A showing the ionic conductivities of 9 polymer electrolytes of the present invention at different temperatures;

[0069] - Figure 2B showing the ionic conductivities of the reference polymer electrolyte at different temperatures;

[0070] - Figure 2C showing the ionic conductivities of another 4 reference polymer electrolytes at different temperatures;

[0071] - Figure 3 showing the ionic conductivities and lithium ionic conductivities of 3 polymer electrolytes of the present invention at 70 °C;

[0072] - Figure 4A and 4B showing the variation of the current density of the button cell containing the polymer electrolyte of the present invention with potential;

[0073] - Figure 5A and 5B showing the variation of the current density of the button cell containing the reference polymer electrolyte with potential;

[0074] - Figure 6 showing the variation of the current density of the button cell containing the first polymer electrolyte of the present invention with potential in six cycles;

[0075] - Figure 7Show the change of current density with potential of the button cell containing the second polymer electrolyte of the present invention in six cycles;

[0076] - Figure 8A 、 8B and 8C show the change of voltage with capacity of the button cell containing the first polymer electrolyte of the present invention at different temperatures;

[0077] - Figure 9A 、 9B and 9C show the change of voltage with capacity of the button cell containing the second polymer electrolyte of the present invention at different temperatures;

[0078] - Figure 10 Show the voltages detected during the repeated charge / discharge cycles of the two polymer electrolytes of the present invention;

[0079] - Figure 11A and 11B Show the discharge capacity and Coulomb efficiency of the first LFP-based lithium metal battery cell containing the polymer electrolyte of the present invention at different temperatures;

[0080] - Figure 12A and 12B Show the discharge capacity and Coulomb efficiency of the first NMC622-based lithium metal battery cell containing the polymer electrolyte of the present invention at different temperatures; and

[0081] - Figure 13A and 13B Show the cycling results of the second LFP-based lithium metal battery cell and the second NMC622-based lithium metal battery cell, each of which contains a lithium salt comprising the polymer electrolyte of the present invention. Detailed Description

[0082] The polymer electrolyte of the present invention comprises a first polyimide polymer, a second polyimide polymer and optionally a plasticizer, or consists essentially of a polyimide polymer, a second polyimide polymer and optionally a plasticizer. The first polyimide polymer advantageously contains a first polyimide repeating unit, or consists essentially of a first polyimide repeating unit. The second polyimide polymer advantageously contains a second polyimide repeating unit, or consists essentially of a second polyimide repeating unit.

[0083] The first polyimide repeating unit is as shown in R 3 (Q) μ as shown.

[0084] μ is independently at least 2, preferably in the range of 2 to 4.

[0085] Q is independently as shown in formula (I):

[0086]

[0087] Advantageously, R 2 is independently C1-C 16 alkyl, preferably C1-C 10 alkyl, more preferably C1-C8 alkyl, most preferably C1-C6 alkyl, such as methyl, ethyl, propyl and butyl. R 2 can be straight-chain or branched.

[0088] As an alternative or in addition, more preferably, R 2 is independently C2-C 16 alkenyl containing one or more C═C bonds, preferably C2-C 10 alkenyl, more preferably C2-C8 alkenyl, most preferably C2-C6 alkenyl. R 2 can be straight-chain or branched.

[0089] As an alternative or in addition, more preferably, R 2 is independently C2-C 16 alkynyl containing one or more C≡C bonds, preferably C2-C 10 alkynyl, more preferably C2-C8 alkynyl, most preferably C2-C6 alkynyl. R 2 can be straight-chain or branched.

[0090] As an alternative or in addition, more preferably, R 2 is independently aryl, such as benzyl or phenyl.

[0091] Advantageously, R 4 is H, C1-C 16 alkyl, C2-C 16 alkenyl or C2-C 16 alkynyl, preferably H, C1-C6 alkyl, C2-C6 alkenyl or C2-C6 alkynyl, most preferably H, C1-C4 alkyl, C2-C4 alkenyl or C2-C4 alkynyl. The alkyl, alkenyl and alkynyl can each be straight-chain or branched.

[0092] A preferred example of Q is:[[]]

[0093] wherein R 4 is H.

[0094] Advantageously, Q is covalently bonded to R 3 via the sulfur atom of Q.

[0095] Advantageously, R 3Independently is a polyether. The term "independently" means that the first polyimide repeating units can be different from each other, for example, containing different R 3 . Advantageously, R 3 is a polyether as shown, where ω is in the range of 0 to 6, preferably in the range of 0 to 4, more preferably in the range of 1 to 4; is in the range of 1 to 4, preferably in the range of 1 to 3, for example 2; and α is in the range of 1 to 10, preferably in the range of 1 to 5, more preferably in the range of 2 to 4.

[0096] For example, R 3 is -(CH2)2(O(CH2)2) α -(i.e., ω is 2, is 2), for example -(CH2)2(O(CH2)2)2-(i.e., α is 2), or -(CH2)2(O(CH2)2)3-(i.e., α is 3).

[0097] As an alternative or in addition, more advantageously, R 3 independently is as C(H) h (C x H 2x+1 ) i ((CH2) ψ ) j (CH2OC(O)(CH2) σ ) k shown. Advantageously, x is in the range of 1 to 6, preferably in the range of 1 to 4, more preferably 1 or 2. Advantageously, ψ is in the range of 1 to 10, preferably in the range of 1 to 8, more preferably in the range of 1 to 6, for example in the range of 1 to 4. Advantageously, σ is in the range of 1 to 20, preferably in the range of 1 to 10, for example in the range of 1 to 6, more preferably in the range of 1 to 4. Additionally, i is in the range of 0 to 2, j and k are independently in the range of 0 to 4. Additionally, h is 4 - i - j - k. The sum of h and i is in the range of 0 to 2.

[0098] For example, R 3 is -(CH2) β , where β is in the range of 1 to 20 (i.e., h is 2, i is 0, j is 2, k is 0, and β is equal to 2*ψ + 1).

[0099] For example, R 3 is C(C2H5)(CH2OC(O)(CH2) σ )3-(i.e., h is 0, i is 1, j is 0, k is 3, and x is 2).

[0100] For example, R 3is C(CH2OC(O)(CH2) σ )4 - (i.e., h is 0, i is 0, j is 0, k is 4, and x is 2).

[0101] The second polyimide unit is shown in formula (II):

[0102]

[0103] Advantageously, R 1 is H, C1 - C 16 alkyl, C2 - C 16 alkenyl or C2 - C 16 alkynyl, preferably H, C1 - C6 alkyl, C2 - C6 alkenyl or C2 - C6 alkynyl, more preferably H, C1 - C4 alkyl, C2 - C4 alkenyl or C2 - C4 alkynyl. The alkyl, alkenyl and alkynyl can each be straight - chain or branched.

[0104] Advantageously, X is H, F, C1 - C 16 alkyl, C1 - C 16 fluoroalkyl, preferably H, F, C1 - C6 alkyl or C1 - C6 fluoroalkyl, more preferably H, F, CH3 or CF3. The alkyl and fluoroalkyl can be straight - chain or branched.

[0105] Advantageously, M + independently is an alkali metal ion. Advantageously, the alkali metal is lithium, sodium or potassium. In other words, the alkali metal ion is advantageously a lithium ion (Li + ), a sodium ion (Na + ), or a potassium ion (K + ).

[0106] Advantageously, m is in the range of 1 to 5.

[0107] A preferred example of the second polyimide repeating unit is the repeating unit shown in formula IV:

[0108]

[0109] wherein R 1 is H, m is 2, M + is Li + (lithium ion), and X is CF3.

[0110] A non - limiting example of the first polyimide polymer is shown in formula V:

[0111]

[0112] wherein

[0113] R 2As defined above, for example, it is CH2;

[0114] R 3 As defined above, where the sum of h and i is 2;

[0115] R 4 is H; and

[0116] s is independently the number of the first polyimide repeating units.

[0117] Another non-limiting example of the polymer electrolyte is shown in Formula VI:

[0118]

[0119] where

[0120] R 2 As defined above, for example, it is CH2;

[0121] R 3 As defined above, where the sum of h and i is 1;

[0122] R 4 is H; and

[0123] s is independently the number of the first polyimide repeating units.

[0124] Yet another non-limiting example of the polymer electrolyte is shown in Formula VII:

[0125]

[0126] where

[0127] R 2 As defined above, for example, it is CH2;

[0128] R 3 As defined above, where h is 0 and i is 0;

[0129] R 4 is H; and

[0130] s is independently the number of the first polyimide repeating units.

[0131] The polymer electrolyte may further comprise a polyimide copolymer comprising or consisting essentially of first and second polyimide repeating units covalently bonded to each other, preferably connected by carbon-carbon bonds.

[0132] Advantageously, the polymer electrolyte is thermally stable at a temperature of at least 75 °C, preferably at least 100 °C or at least 125 °C.

[0133] Advantageously, the polymer electrolyte has an ionic conductivity of at least 0.25 mS / cm at 70 °C, preferably at least 0.3 mS / cm, more preferably at least 0.4 mS / cm.

[0134] Advantageously, the polymer electrolyte has an oxidation stability of at least 3 V at 70 °C, preferably at least 4 V.

[0135] Advantageously, the polymer electrolyte of the present invention is self-standing. The terms "self-standing" and "self-supporting" are used interchangeably and mean that a film, substrate, product or article has sufficient mechanical strength to be handled, such as cut, shaped or processed, without the need to place the film on a carrier or support to avoid damage.

[0136] The polymer electrolyte of the present invention is advantageously prepared (i.e., produced or manufactured) by the method disclosed herein.

[0137] In a first step, a blend is prepared. The blend comprises a third poly(maleimide) polymer containing a third poly(maleimide) repeating unit, a second poly(maleimide) polymer containing a second poly(maleimide) repeating unit, a thiol-ene reagent, and a free radical initiator.

[0138] Optionally, the blend further comprises a plasticizer. Optionally, the blend further comprises a processing solvent.

[0139] The third poly(maleimide) repeating unit has a pendant vinyl group and is as shown in Formula III:

[0140]

[0141] wherein R 2 and R 4 are advantageously as defined above.

[0142] Advantageously, the number n of the third poly(maleimide) repeating units contained in the third poly(maleimide) polymer is in the range of 10 to 10,000, preferably in the range of 100 to 7500, more preferably in the range of 500 to 4000.

[0143] Advantageously, the number average molecular weight of the third poly(maleimide) polymer is in the range of 1 kDa to 1500 kDa, preferably in the range of 15 kDa to 1000 kDa, more preferably in the range of 75 kDa to 800 kDa.

[0144] The second poly(maleimide) repeating unit is as shown in Formula II. Advantageously, the number p of the second poly(maleimide) repeating units contained in the second poly(maleimide) polymer is in the range of 10 to 10,000, preferably in the range of 100 to 7500, more preferably in the range of 500 to 4000.

[0145] Advantageously, the number-average molecular weight of the second polyimide polymer is in the range of 3 kDa to 2000 kDa, preferably in the range of 100 kDa to 1750 kDa, more preferably in the range of 250 kDa to 1500 kDa.

[0146] A first example of the third polyimide polymer is shown in Formula VIII:

[0147]

[0148] where R 2 is CH2, and R 4 is as defined above, for example, H.

[0149] A second example of the third polyimide polymer is shown in Formula IX:

[0150]

[0151] where R 2 is benzyl, and R 4 is as defined above, for example, H.

[0152] An example of the second polyimide polymer is shown in Formula XIV:

[0153]

[0154] where R 1 is as defined above, for example, H, and where m is 2, M + is Li + (lithium ion), and X is CF3.

[0155] The thiol-ene reagent contains thiol groups. The number q of thiol groups is at least 2, for example, 2, 3, 4 or greater. Advantageously, the thiol-ene reagent is as shown in R 3 (SH) μ where R 3 and μ are as defined above.

[0156] Non-limiting examples of the thiol-ene reagent include, but are not limited to: those compounds shown in Formula X (q = 2), Formula XI (q = 2), Formula XII (q = 3) and Formula XIII (q = 4):

[0157]

[0158] where α is in the range of 1 to 10, preferably in the range of 1 to 5, more preferably in the range of 2 to 4, for example, 2, 3 or 4;

[0159]

[0160] where β ranges from 1 to 20, preferably from 2 to 18, more preferably from 5 to 15, for example from 8 to 12, for example 10;

[0161]

[0162] where γ, δ and ε independently range from 0 to 19, preferably from 0 to 10, more preferably from 0 to 4;

[0163] and

[0164]

[0165] where η, θ, λ and ξ independently range from 0 to 19, preferably from 0 to 10, more preferably from 0 to 4.

[0166] A preferred example of the free radical initiator is 2-hydroxy-2-methylpropiophenone.

[0167] The present inventors have found that the presence of a processing solvent in the blend is optional. The advantage of the optional presence of a processing solvent is to reduce the cost of the blend and the polymer electrolyte, make the method for preparing the polymer electrolyte less complex (i.e., fewer processing steps), and not require further (processing) solvent recovery and recycling, and reduce environmental impact.

[0168] However, depending on the actual composition of the blend, a processing solvent can be added to optimize the performance in terms of conversion to the polymer electrolyte. Therefore, whether to add a processing solvent to the blend depends on the types and amounts of the third and second polymaleimide repeat units, the thiol-ene reactant, the free radical initiator, and the optional plasticizer.

[0169] When the blend contains a processing solvent, the processing solvent advantageously comprises acetone, dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, or a combination of two or more thereof, or consists essentially of the same.

[0170] When the blend contains a plasticizer (i.e., a plasticizing agent), the plasticizer advantageously is selected from linear carbonates, cyclic carbonates, ethers, and nitriles. Particularly preferred examples of the plasticizer are propylene carbonate and ethylene carbonate. The blend can contain two or more plasticizers, which are independently selected from linear carbonates, cyclic carbonates, ethers, and nitriles.

[0171] Optionally, the blend further comprises a crosslinking agent. Non-limiting examples of crosslinking agents include polyethylene glycol diacrylate (PEGDA), trimethylolpropane triacrylate (TMPTA), pentaerythritol tetraacrylate (PETA), butyl acrylate (BA).

[0172] Optionally, the blend further comprises a metal salt. Advantageously, when the blend comprises a metal salt, the metal is advantageously lithium, sodium, magnesium or aluminum.

[0173] Advantageously, the blend comprises 0 - 10 wt% of a metal salt, such as 0.1 - 7.5 wt%, preferably 0.2 - 5 wt%, more preferably 0.5 - 5 wt%, based on the total weight of the blend minus the weight of any optional processing solvent.

[0174] Advantageously, the blend is applied to a substrate, thereby obtaining a film of the blend. Advantageously, the film has a thickness of 10 μm to 1000 μm, preferably 20 μm to 750 μm, more preferably 25 μm to 500 μm, such as 50 μm to 250 μm. It should be understood that the thickness can vary based on the target or desired thickness of the polymer electrolyte. Advantageously, the target or desired thickness is determined according to the desired total cell resistance and the desired mechanical properties, such as mechanical strength and flexibility.

[0175] Advantageously, when the blend comprises a processing solvent, the processing solvent is removed after the blend is applied to the substrate and before the blend (substantially free of processing solvent) is exposed to one or more of UV irradiation, IR irradiation or a temperature of up to 100 °C.

[0176] Advantageously, the processing solvent is removed by heating the substrate comprising the blend to a temperature of 20 °C to 100 °C, preferably 20 °C to 50 °C.

[0177] Advantageously, when the blend comprises a plasticizer, the substrate is heated to a temperature below the maximum continuous use temperature of the plasticizer, where the maximum continuous use temperature is defined by the relative thermal index (RTI) of Underwriter Laboratories (UL746B), preferably heated to a temperature in the range of 20 °C to T v -10 °C, where T v is the maximum continuous use temperature of the plasticizer, as defined by the relative thermal index (RTI) of Underwriter Laboratories (UL 746B). By operating in this way, evaporation and / or removal of the plasticizer is avoided.

[0178] As an alternative or in addition, advantageously, the processing solvent is removed by exposing the substrate comprising the blend to an atmosphere at a pressure below atmospheric pressure.

[0179] Advantageously, when applying a pressure below atmospheric pressure, the pressure is 975 mbar or lower, preferably 950 mbar or lower, more preferably 930 mbar or lower, such as 900 mbar or lower, 750 mbar or lower, or 500 mbar or lower.

[0180] It should be understood that the optimal temperature and / or pressure for evaporating the processing solvent depends on the composition of the blend. In particular, when the blend contains a plasticizer, the optimal conditions for evaporating the processing solvent depend on the plasticizer used, and advantageously the conditions are selected to avoid evaporation or degradation of the plasticizer.

[0181] The processing solvent is preferably acetone. Acetone is particularly preferred because it has a relatively low boiling point (i.e., 56 °C at atmospheric pressure) and a relatively high vapor pressure (i.e., 230 mmHg at 25 °C). Its boiling point and vapor pressure allow for the removal of acetone by heating to a moderate temperature, such as about 40 °C to 65 °C at atmospheric pressure, preferably 50 °C to 60 °C at atmospheric pressure, and / or at a pressure slightly below atmospheric pressure, such as about 950 mbar.

[0182] Advantageously, the blend (substantially free of the processing solvent) is exposed to one or more of UV irradiation, IR irradiation, or a temperature up to 100 °C, which initiates the thiol-ene reaction of the thiol-ene reactant with the third polyimide repeat unit, thereby obtaining a first polyimide polymer containing or consisting of the first polyimide repeat unit shown in Formula I.

[0183] In other words, when the blend (substantially free of the processing solvent) is exposed to one or more of UV irradiation, IR irradiation, or a temperature up to 100 °C, the blend is converted into a polymer electrolyte, particularly the polymer electrolyte of the present invention, which contains the first and second polyimide polymers as defined above, namely: a first polyimide polymer containing the first polyimide repeat unit shown in Formula I, and a second polyimide polymer containing the second polyimide repeat unit shown in Formula II.

[0184] Examples

[0185] Example 1

[0186] Nine blends were prepared, which contained the same components but in different amounts. Table 1 shows the weight percentages of the components in all nine blends. For all blends, is 1, where n is the number of the third polyimide repeat units, q is the number of thiol groups, and a is the number of thiol-ene reactant molecules.

[0187] These blends contain a third polyimide polymer containing a third polyimide repeating unit as shown in Formula III, where R 2 is CH2, and R 4 is H. The third polyimide polymer (designated as "3rd" in Table 1) has a number average molecular weight in the range of 100 kDa to 650 kDa.

[0188] These blends contain a second polyimide polymer containing a second polyimide repeating unit as shown in Formula II (designated as "2nd" in Table 1), where R 1 is H, m is 2, M + is Li + , X is CF3, and the number average molecular weight is in the range of 250 kDa to 1500 kDa.

[0189] The thiol-ene reagent (designated as "2SH" in Table 1) contains 2 thiol groups and is as shown in Formula X, where α is 2 and the molecular weight is 182 Da.

[0190] The plasticizer (designated as "PC" in Table 1) is propylene carbonate with a molecular weight of 102 Da, and the radical initiator (designated as "Ini" in Table 1) is 2-hydroxy-2-methylpropiophenone with a molecular weight of 164 Da.

[0191] Table 1: Composition of the blends, expressed as weight % based on the total weight of the blend minus the weight of the solvent acetone

[0192] Compound number No. 3rd 2nd 2SH PC Ini 1 3.8 34.0 2.2 59.9 0.1 2 7.2 28.6 4.1 59.7 0.4 3 10.1 23.6 6.1 59.7 0.5 4 12.8 19.4 7.5 59.6 0.7 5 15.3 15.3 9.1 59.5 0.8 6 17.6 11.8 10.2 59.5 0.9 7 19.7 8.4 11.5 59.4 1.0 8 21.6 5.4 12.6 59.3 1.1 9 23.4 2.6 13.5 59.3 1.2

[0193] Acetone, used as a processing solvent, is added to the nine blends shown in Table 1 in an amount such that the blends contain 86 wt% acetone, based on the total weight of the blend including the weight of acetone. The acetone-containing blends are then applied to a Teflon substrate by casting, more particularly solvent casting.

[0194] The Teflon substrate containing the blend is placed in an argon chamber, and an argon gas flow is supplied to the substrate at room temperature and atmospheric pressure for a period of 24 hours to remove acetone.

[0195] Subsequently, the substantially solvent-free blend is exposed to UV irradiation, which initiates the thiol-ene reaction, thereby obtaining a polymer electrolyte membrane with a thickness of 150 - 200 μm. These membranes are self-standing. In other words, these membranes have sufficient mechanical strength for handling and no longer require the use of the Teflon substrate as a support material (see Figure 1 ).

[0196] Four reference polymer electrolytes are also prepared.

[0197] The first reference electrolyte is prepared from a blend comprising the second polyimide polymer and a plasticizer among the nine blends of the present invention, poly(ethylene glycol) diacrylate (PEGDA, number average molecular weight of 700 g / mol) used as a crosslinking agent, and poly(vinylidene fluoride - hexafluoropropylene) copolymer (PVdF - HFP) used as a mechanical carrier. These reference blends are then polymerized by free radical polymerization. The resulting polymer electrolyte contains 7.3 wt% of the second polyimide polymer, 5 wt% of the PVdF - HFP copolymer, 17.6 wt% of PEGDA, and 70.1 wt% of the plasticizer based on the total weight of the electrolyte.

[0198] The other three reference electrolytes contain the second polyimide polymer and poly(ethylene glycol) dimethyl ether - M W 500 (PEGDME) in a 5M poly(ethylene oxide) (PEO) powder in acetonitrile solution. These three reference electrolytes all have a ratio of ethylene oxide units to lithium ions of 20, and the weight ratios between PEO and PEGDME are 20 / 80, 30 / 70, and 40 / 60, respectively.

[0199] Example 2

[0200] Using a BT Lab potentiostat (Bio - Logic Science Instruments), the ionic conductivities of the nine polymer electrolytes of the present invention, four reference polymer electrolytes (all prepared as described in Example 1), and 100% poly(ethylene oxide) (PEO) as a standard sample were detected by alternating current (AC) impedance spectroscopy. This detection was carried out at temperatures varying between 25 °C and 70 °C in the frequency range from 10 kHz to 0.1 Hz. Ionic conductivity is a means of measuring the suitability of polymer electrolytes for battery cells.

[0201] Figure 2A An Arrhenius plot showing the ionic conductivities (in S / cm) of the nine polymer electrolytes of the present invention. Figure 2B An Arrhenius plot showing the first reference electrolyte. Figure 2C An Arrhenius plot showing the ionic conductivities of the 2nd - 4th reference electrolytes (samples 20 / 80, 30 / 70, and 40 / 60) and the PEO standard sample (sample 100 / 0), respectively.

[0202] From Figure 2B and Figure 2CAs can be seen, all four reference electrolytes show qualified to good ionic conductivity values, while the ionic conductivity value of the 100% PEO sample is very low and below the acceptable value, which is as expected. The ionic conductivity values of the four reference electrolytes are in the range of 2*10 -7 S / cm to 1.5*10 -5 S / cm at 25 °C and in the range of 2*10 - 5 S / cm to 4*10 -5 S / cm at 70 °C.

[0203] All nine electrolytes of the present invention ( Figure 2A ) show high ionic conductivity, several orders of magnitude higher than the ionic conductivity of the reference electrolytes at each temperature. The ionic conductivity values of the electrolytes of the present invention are in the range of 1.5*10 -5 S / cm to 10 -4 S / cm at 25 °C and in the range of 6*10 -5 S / cm to 4*10 -4 S / cm at 70 °C. It should be noted that the samples with a lower amount of the first polymaleimide polymer have a higher ionic conductivity. A lower amount of the first polymaleimide polymer means a higher amount of lithium cations in the electrolyte, which can account for the higher ionic conductivity.

[0204] Example 3

[0205] The lithium transference number and lithium ionic conductivity of the polymer electrolytes obtained from the blends No. 2, No. 3 and No. 5 of Table 1 and Example 1 and four reference polymer electrolytes were measured. The Li transference number was measured by a combination of the AC impedance detection method and the DC polarization method described in "Electrochemical Detection of Transference Numbers in Polymer Electrolytes", Evans et al., Polymers, Vol. 28, 13 (1987), pp. 2324-2328. For this purpose, a lithium symmetric cell was used, which had the polymer electrolyte as the electrolyte. The temperature of the cell was controlled at 70 °C by a temperature-controlled chamber. The lithium transference number was calculated according to Equation 1:

[0206]

[0207] where

[0208] I0 and I s are the corresponding initial current and steady-state current,

[0209] R bo and R bs are the corresponding initial resistance and final resistance of the electrolyte body,

[0210] R io and R is are the corresponding initial and final resistances of the interfacial layer between the Li° electrode / electrolyte, and

[0211] ΔV is the applied DC voltage.

[0212] The Li conductivity is obtained by multiplying the total ionic conductivity of the electrolyte by the lithium transference number. The lithium transference number is defined as the ratio of the current generated by the lithium cations in the polymer electrolyte to the total current. When the lithium transference number is close to 1, this implies that the ionic conduction performance in the polymer electrolyte is mainly accomplished by the lithium cations. Table 2 lists the calculated lithium transference numbers of the three tested polymer electrolytes.

[0213] Table 2: Calculated lithium transference numbers

[0214] Electrolyte Li transference number Obtained from compound 2 0.63±0.10 Obtained from compound 3 0.70±0.05 Obtained from compound 5 0.80±0.02 Reference 1 (PVdF-HFP) 0.83±0.10 Reference 2 (20 / 80) 0.96 Reference 3 (30 / 70) 0.93 Reference 4 (40 / 60) 0.95

[0215] As can be seen from Table 2, the three polymer electrolytes of the present invention and the reference electrolyte show high lithium transference numbers, and a value of at least 0.5 is considered high in the art.

[0216] The Li conductivity is a means to measure the conductivity achieved by the lithium cations. In other words, a higher transference number implies a smaller difference between the ionic conductivity (detected in Example 2) and the Li conductivity. Figure 3 Shows the Li conductivity (σ Li + ) of the three tested polymer electrolytes (obtained from blends No. 2, No. 3, and No. 5) compared to the ionic conductivity (σ 总 ), which was measured at 70 °C. As can be seen from Figure 3 , a high Li conductivity of at least 2*10 -4 S / cm was measured. Additionally, in terms of the difference between the ionic conductivity and the Li conductivity, the polymer electrolyte obtained from blend No. 5 was the smallest. This is in line with this polymer electrolyte showing the highest lithium transference number.

[0217] Example 4

[0218] The electrochemical anodic stability was detected by linear sweep voltammetry in a VMP3 potentiostat at 70 °C. A two-electrode configuration was used, with a lithium foil as the reference electrode and the counter electrode. For this purpose, a CR2032 coin cell was prepared, which had a lithium foil as the reference electrode and the counter electrode, and stainless steel as the working electrode. The polymer electrolytes used in the coin cell were obtained from blends No. 3 and No. 5 in Example 1 and reference electrolyte 1 and reference electrolyte 4 (40 / 60). All other components of the CR2032 coin cell were those commonly used in the art. The coin cell was assembled in an argon glove box.

[0219] Linear sweep voltammetry was performed from the open circuit voltage (OCV) to 6.0 V vs. Li + / Li at a scan rate of 1 mV / s.

[0220] Figure 4A and Figure 4B show the variation of the current density measured for button cells, which button cells contain polymer electrolytes obtained from compounding mixtures No. 3 and No. 5, respectively. Figure 5A and Figure 5B show the variation of the current density measured for button cells, which button cells contain reference polymer electrolytes 1 and 4, respectively. It should be noted that for the polymer electrolyte of the present invention and reference electrolyte 1, irreversible oxidation of the system starts to occur at about 5.0 V, which means that for battery applications, the polymer electrolyte can be combined or used in conjunction with active materials operating at voltages below 5.0 V. However, for reference electrolyte 4 ( Figure 5B ), irreversible oxidation of the system starts to occur at about 3.7 V.

[0221] The electrochemical cathodic stability of the polymer electrolyte obtained in Example 1 was detected by cyclic voltammetry at 70 °C. For this purpose, two CR2032 type button cells were prepared, each having a lithium foil as the reference electrode and the counter electrode, and a copper foil as the working electrode. As the electrolyte, polymer electrolytes obtained from compounding mixtures No. 3 and No. 5 were used (each button cell used a single electrolyte). All other components of the CR2032 type button cells are those commonly used in the art. The button cells were assembled in an argon glove box.

[0222] Cyclic voltammetry included scanning 6 times at a scan rate of 1 mV / s in the voltage range of 3.00 V to -0.05 V vs. Li + / Li.

[0223] Figure 6 and Figure 7 show the variation of the current density measured for button cells in each of the 6 cycles, which button cells contain polymer electrolytes obtained from compounding mixtures No. 3 and No. 5, respectively. During the reduction process of these two polymer electrolytes, an intensity response appeared during the first cycle. This can be attributed to the reduction of the plasticizer at these voltages, which is an irreversible reduction. The 2nd to 6th cycles showed a stable current density distribution.

[0224] The critical current density test was also carried out using a VMP3 potentiostat. For this purpose, two CR2032 coin cells were prepared, each having a lithium foil as the cathode and anode (i.e., symmetric coin cells). As the electrolyte, a polymer electrolyte obtained from blends No. 3 and No. 5 was used (a single electrolyte was used for each coin cell). All other components of the CR2032 coin cell were those commonly used in the art. The coin cells were assembled in an argon glove box.

[0225] The critical current density test was carried out by cycling the coin cell in a constant current mode, where the current density could vary between 0.1 mA / cm2 and 5 mA / cm2, while simultaneously maintaining the total capacity constant at 0.2 mAh / cm2.

[0226] Figure 8A 、 8B Figures 8C show the variation of the voltage measured for a coin cell containing a polymer electrolyte obtained from blend No. 3, where the measurements were made at 70 °C, 40 °C, and 25 °C, respectively. It was observed that the situation was stable up to a current density of 5C = 1.0 mA / cm2 at 70 °C, 3C = 0.61 mA / cm2 at 40 °C, and 1C = 0.2 mA / cm2 at 25 °C.

[0227] Figure 9A 、 9B Figures 9C show the variation of the voltage measured for a coin cell containing a polymer electrolyte obtained from blend No. 5, where the measurements were made at 70 °C, 40 °C, and 25 °C, respectively. It was observed that the situation was stable up to a current density of 5C = 1.0 mA / cm2 at 70 °C, 3C = 0.61 mA / cm2 at 40 °C, and 1C = 0.4 mA / cm2 at 25 °C.

[0228] In addition, CR2032 symmetric coin cells containing polymer electrolytes obtained from blends No. 3 and No. 5 (a single electrolyte was used for each coin cell) were tested by repeated charge / discharge (cycling test) at a constant current density of 0.61 mA / cm2 at 70 °C, while simultaneously maintaining the total capacity constant at 0.2 mAh / cm2. Two different types of lithium foils, designated A and B, were used. Type A was a pristine lithium metal foil with a thickness of 500 μm. Type B was a lithium metal layer cast on top of a copper foil with a thickness of 50 μm. Figure 10 show the variation of the voltage with the cycling test time. As can be seen from Figure 10 all the battery cells showed a stable voltage condition for more than 800 hours.

[0229] Example 5

[0230] Assemble the first lithium metal battery cell using the polymer electrolyte obtained from Blend No. 3 in Example 1. Based on the total weight of the cathode, the cathode contains 80 wt% of LiFePO4 (LFP), 10 wt% of the second polyimide polymer as described in Example 1, and 10 wt% of carbon black. This active material loading makes the theoretical capacity of the battery cell close to 1 mAh / cm2. The voltage window of LFP is known to be between 2.7 V and 3.8 V. The anode is a copper foil coated with lithium metal doped with 0.3 wt% aluminum.

[0231] The first lithium metal battery cell is tested through repeated charge / discharge cycles, reaching 100 cycles at 70 °C ( Figure 11A ) and 50 cycles at 40 °C ( Figure 11B ). As can be seen from Figure 11A and 11B , stable cycling is observed, which is independent of the temperature at which the test is conducted. The capacity retention rate is 99%, which is excellent. The specific capacity obtained in the test is close to the theoretical value, and as can be seen from Figure 11A and 11B , these battery cells are stable throughout the cycling period.

[0232] Assemble the second lithium metal battery cell using the polymer electrolyte obtained from Blend No. 3 in Example 1 as the electrolyte. Based on the total weight of the cathode, the cathode contains 80 wt% of NMC 622 (nickel manganese cobalt), 10 wt% of the second polyimide polymer as described in Example 1, and 10 wt% of carbon black. This active material loading makes the theoretical capacity of the battery cell close to 1 mAh / cm2. The voltage window of NMC 622 is known to be between 3.0 V and 4.25 V. The anode is a copper foil coated with lithium metal doped with 0.3 wt% aluminum.

[0233] The second lithium metal battery cell is tested through repeated charge / discharge cycles, reaching 100 cycles at 70 °C ( Figure 12A ) and 50 cycles at 40 °C ( Figure 12B ). As can be seen from Figure 12A and 12B , although slightly lower than the first lithium metal battery cell, the capacity retention rate is still high. Although a limited but constant capacity loss is observed in each charge / discharge cycle, it is clearly visible that the polymer electrolyte of the present invention can be used with active materials operating at high voltages with excellent performance.

[0234] Example 6

[0235] Another blend of the present invention is prepared by adding 0.12 g of the third polymaleimide polymer as described in Example 1, 0.48 g of the second polymaleimide polymer as described in Example 2, 0.083 g of pentaerythritol tetra(2-mercaptoacetate) as a thiol-ene reagent (the thiol-ene reagent shown in Formula V, where η, θ, λ, and ξ are all 0), 0.6953 g of propylene carbonate and 0.3275 g of ethylene carbonate as plasticizers, and 2-hydroxy-2-methylpropiophenone as a radical initiator to acetone as a solvent.

[0236] Additionally, 0.0853 g of lithium bis(fluorosulfonyl)amide is added as a lithium salt, corresponding to 4.76 wt% based on the total weight of the blend excluding the weight of acetone.

[0237] The amount of acetone used is such that the blend contains 86 wt% acetone, based on the total weight of the blend including the weight of acetone.

[0238] Then, the blend containing acetone is applied to a Teflon substrate by casting, more particularly solvent casting.

[0239] The Teflon substrate containing the blend is placed in an argon chamber, and an argon gas flow is supplied to the substrate at room temperature and atmospheric pressure for 24 hours to remove acetone.

[0240] Subsequently, the blend substantially free of solvent is exposed to UV irradiation, which initiates the thiol-ene reaction, thereby obtaining a polymer electrolyte membrane with a thickness of 150 - 200 μm.

[0241] Using this polymer electrolyte membrane as an electrolyte, the first lithium metal battery cell is assembled. Based on the total weight of the cathode, the cathode contains 80 wt% of LiFePO4 (LFP), 10 wt% of the second polymaleimide polymer, and 10 wt% of carbon black. This active material loading makes the theoretical capacity of the battery cell close to 1 mAh / cm2. The voltage window of LFP is known to be between 2.7 V and 3.8 V. The anode is a copper foil coated with lithium metal doped with 0.3 wt% aluminum.

[0242] Using this polymer electrolyte membrane as an electrolyte, the second lithium metal battery cell is assembled. Based on the total weight of the cathode, the cathode contains 80 wt% of NMC 622 (nickel manganese cobalt), 10 wt% of the second polymaleimide polymer, and 10 wt% of carbon black. This active material loading makes the theoretical capacity of the battery cell close to 1 mAh / cm2. The voltage window of NMC 622 is known to be between 3.0 V and 4.25 V. The anode is a copper foil coated with lithium metal doped with 0.3 wt% aluminum.

[0243] These lithium metal battery cells were tested through repeated charge / discharge cycles, reaching 40 cycles at 40 °C (first type of battery cell, Figure 13A ) and reaching 60 cycles (second type of battery cell, Figure 13B ). As can be seen from Figure 13A and 13B , the Coulombic efficiency (or capacity retention rate) is very high. Although a limited but constant capacity loss was observed in each charge / discharge cycle, it is clearly visible that the polymer electrolyte of the present invention can be used together with active materials operating at high voltages with excellent performance.

Claims

1. A polymer electrolyte for a battery cell, comprising: - a first polymaleimide polymer comprising a first polymaleimide repeating unit, wherein the first polymaleimide repeating unit is R 3 (Q) μ As shown, in R 3 independently C(H) h (C x H 2x+1 ) i ((CH2) ψ ) j (CH2OC(O)(CH2) σ ) k or polyether, wherein i is in the range of 0 to 2; j and k are independently in the range of 0 to 4; h is 4-ijk; the sum of h and i is in the range of 0 to 2; x is in the range of 1 to 6; ψ is in the range of 1 to 10; and σ is in the range of 1 to 20; μ is independently at least 2, preferably in the range of 2 to 4; and Q is independently represented by formula (I): in R 2 Independently C1-C 16 Alkyl, C2-C 16 Alkenyl, C2-C 16 Alkynyl or aryl; R 4 independently H, C1-C 16 Alkyl, C2-C 16 Alkenyl, C2-C 16 Alkynyl; and Q is covalently bonded to R via the sulfur atom of Q 3 ; - A second polymaleimide polymer containing a second polymaleimide repeating unit represented by formula (II): in R 1 independently H, C1-C 16 Alkyl, C2-C 16 Alkenyl, C2-C 16 Alkynyl; m is independently 1 to 5; M + are independently alkali metal ions; and X is independently H, F, C1-C 16 Alkyl, C1-C 16 Fluoroalkyl. 2 . The polymer electrolyte according to claim 1 , wherein the molar ratio between the first polymaleimide polymer and the second polymaleimide polymer is in the range of 5 to 95, preferably in the range of 20 to 50.

3. A polymer electrolyte according to any one of the preceding claims, wherein R 2 It is methyl, ethyl, propyl, n-butyl, isobutyl, benzyl or styryl.

4. The polymer electrolyte according to any one of the preceding claims, wherein the alkali metal ions are lithium ions.

5. A polymer electrolyte according to any one of the preceding claims, wherein X is CF3, CH3 or F.

6. A polymer electrolyte according to any one of the preceding claims, wherein R 3 Yes The polyethers shown, wherein ω is in the range of 0 to 4, is in the range of 1 to 4, and α is in the range of 1 to 10.

7. A polymer electrolyte according to any one of the preceding claims, wherein R 3 Yes - (CH2) β -, C(CH2CH3)(CH2OC(O)(CH2) σ )3-, or C(CH2OC(O)(CH2) σ )4-, wherein β is in the range of 1 to 20, and σ is in the range of 1 to 20.

8. The polymer electrolyte according to any one of the preceding claims, further comprising 0.5 to 90 wt. %, preferably 30 to 80 wt. %, of a plasticizer, based on the total weight of the polymer electrolyte.

9. The polymer electrolyte according to claim 8, wherein the plasticizer is selected from the group consisting of linear carbonates, cyclic carbonates, ethers and nitriles.

10. A battery cell comprising a polymer electrolyte according to any one of the preceding claims.

11. A method for preparing a polymer electrolyte for a battery cell, wherein the polymer electrolyte comprises a first polymaleimide polymer and a second polymaleimide polymer, the method comprising: - Prepare a compound containing the following components: ○ A third polymaleimide polymer containing a third polymaleimide repeating unit, wherein the third polymaleimide repeating unit is represented by formula (III): in R 2 Independently C1-C 16 Alkyl, C2-C 16 Alkenyl, C2-C 16 alkynyl or aryl; and R 4 independently H, C1-C 16 Alkyl, C2-C 16 Alkenyl, C2-C 16 Alkynyl; ○ A second polymaleimide polymer containing a second polymaleimide repeating unit, wherein the second polymaleimide repeating unit is as shown in formula (II); o a thiol-ene reactant comprising q thiol groups, wherein q is at least 2; o a free radical initiator; and o Optionally, a processing solvent; - applying the compound to a substrate; - when the compound comprises a processing solvent, removing the processing solvent, thereby obtaining a compound substantially free of processing solvent; and - initiating a thiol-ene reaction of the thiol-ene reactant with the third polymaleimide repeating unit by exposing the (substantially free of processing solvent) compound to one or more of UV radiation, IR radiation or a temperature of up to 100° C., thereby obtaining a polymer electrolyte, Features wherein a is the number of thiol-ene reactant molecules and n is the number of third polymaleimide repeating units in the compound.

12. The method of claim 11, wherein the compound further comprises a plasticizer.

13. The method of any one of claims 11 to 12, wherein the compound comprises 0-80 wt% plasticizer, 3-45 wt% combined of the third polymaleimide polymer and the thiol-ene reactant, 1-45 wt% of the second polymaleimide polymer, and 0.05-1.5 wt% free radical initiator, based on the total weight of the compound minus the weight of the optional solvent.

14. The method of any one of claims 11 to 13, wherein the optional processing solvent comprises acetone, dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, or a combination of two or more thereof.

15. The method according to any one of claims 11 to 14, wherein the compound comprises 0-95 wt%, preferably 10-90 wt% of processing solvent, based on the total weight of the compound including the weight of the processing solvent.

Citation Information

Patent Citations

  • Cross-linked solid-polymer electrolytes, methods of making same, and uses thereof

    US20230096123A1

  • Precursor composition for polymer electrolyte, and gel polymer electrolyte formed therefrom

    WO2022055307A1